(untitled) (Jurnal Mekanikal, 2018)
The level of stress utilisa tion within structural elements due to external and transf erred loads between structural members may be estimated. This may routinely be performed at early design stages where all loading parameters and assumptions are p redicted to act on the structure that results the response under normal operating condition. 771e paper addresses loading parameters. discuss analysis steps that have been applied to the structure and illustrate subsequent results ofthe stress utilisation within the structure due to the response to external and transf erred load acting on the structure. Particular application includes the studies on typical shallows or medium water depth jacket structures under normal and extreme loading conditions.